2011
DOI: 10.1161/circheartfailure.110.958512
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Carvedilol in the Treatment of Chronic Aortic Valve Regurgitation

Abstract: Background-Aortic regurgitation (AR) is a chronic disease for which there is currently no approved medical treatment.We previously reported in an animal model that ␤-blockade with metoprolol exerted beneficial effects on left ventricular remodeling and survival. Despite the recent publication of promising human data, ␤-blockade in chronic AR remains controversial. More data are needed to support this potentially new treatment strategy. We hypothesized that carvedilol might be another safe treatment option in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
(17 reference statements)
2
28
0
1
Order By: Relevance
“…In a murine model of severe AR, Plante and colleagues showed that after 180 days, the end systolic diameter was smaller and the LVEF higher in rats treated with metoprolol compared with untreated animals, whereas the end diastolic diameter was not significantly different 17. Similar results were found by Zendaoui and co-workers 19. These results suggest that β-blocker therapy does indeed protect the LV in AR.…”
Section: Discussionsupporting
confidence: 55%
“…In a murine model of severe AR, Plante and colleagues showed that after 180 days, the end systolic diameter was smaller and the LVEF higher in rats treated with metoprolol compared with untreated animals, whereas the end diastolic diameter was not significantly different 17. Similar results were found by Zendaoui and co-workers 19. These results suggest that β-blocker therapy does indeed protect the LV in AR.…”
Section: Discussionsupporting
confidence: 55%
“…To our knowledge it is the first report of a pharmacological treatment influencing LV remodeling in an animal model but with little influence on LV hypertrophy (Plante et al 2004a,b;Plante et al 2009;Plante et al 2008;Zendaoui et al 2011). However, considering the short duration of our study, it is not totally excluded that a preventive effect on LVH would appear after a longer follow-up.…”
Section: Discussionmentioning
confidence: 68%
“…Para los pacientes que después de la cirugía siguen sufriendo insuficiencia cardiaca o hipertensión, son útiles los inhibidores de la enzima de conversión de la angiotensina (IECA), los antagonistas del receptor de la angiotensina II (ARA-II) y los bloqueadores beta 68,69 . En pacientes con síndrome de Marfan, los bloqueadores beta y el losartán pueden reducir la dilatación de la raíz aórtica y el riesgo de complicaciones aórticas, por lo que se debe considerarlos antes y después de la cirugía [70][71][72] .…”
Section: Tratamiento Médicounclassified